Putin’s Coming Presidency : Tougher for Russo - Western Relations? - Cheang, Chris (2018)
President Putin’s annual address to the Federal Assembly on 1 March 2018 places the onus on the West to improve the current tense relationship. What is the Russian leader trying to achieve?